Acceptability of Sepat Shredded Formulation - Yuliani, Alfira; Alya, Nanda Nabilah; Khairunnisa, Rania Allima; Kumalasari, Isti (Journal of Applied Food and Nutrition, 2023)
Background: Stunting is a condition where a child's growth and development is disrupted caused by a short or very short body based on the Body Length by Age (PB/U) or Height by Age (TB/U) index. One of the causes of stunting in Indonesia is insufficient intake of animal protein. Animal protein acts as a macronutrient that has more complete essential amino acids to activate growth hormone. Fish is a source of animal protein that is easy to obtain and cheap. Sepat fish is a species that is often found in West Bandung Regency. The aim of this research is to analyze the acceptability of toddlers to shredded Sepat in West Bandung Regency.Research Methods: This research uses an experimental method with two formulations. Formula (F1) uses 100% Sepat fish as the basic ingredient and Formula (F2) uses a mixture of Sepat fish and grated coconut in a 1:1 ratio. The hedonic test was carried out on 20 panelists who tasted both formulas. The analysis was carried out descriptively.Research Result: The results of the analysis of F1 show average values for color (3), flavor (3.25), taste (3), and texture (3.65). Average F2 values for color (3.3), flavor (3.3), taste (2.85), and texture (3.55). In terms of preference for the acceptability of Sepat fish floss, panelists preferred F2 with an average value of 3.2 compared to F1 with an average value of 2.95.Conclusion: Sepat fish floss is an innovative processed product that is easy to make and is not yet sold commercially in Indonesia. Sepat fish floss can be used as an alternative to fulfill animal protein because it is affordable, easy to access, and has good acceptability.